EFEKTIVITAS BERKUMUR LARUTAN DAUN BINAHONG TERHADAP INDEKS PLAK PADA SISWA KELAS III – IV ANAK SEKOLAH DASAR NEGERI 21 MANADO KOTA MANADO - Jeineke Ratuela; Anneke Tahulending (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Dental plaque is a soft deposit that adheres tightly to the surface of the teeth, consisting of icroorganisms that multiply in an intercellular matrix if a person neglects dental and oral hygiene. Anredera cordifolia (Ten) Steenis or commonly known as binahong or gondola is a creeping plant that is perennial (long-lived). The benefits of the binahong leaf plant are enormous in the world of medicine, empirically binahong can cure various types of diseases. In medicine, the part of the plant used can come from the leaves. Research using boiled leaves has found many ingredients, which were stated by (Setiaji, 2009) that flavonoids have various effects, namely analgesic, anti-inflammatory and as a vasolidator. The aim of this research was to determine the effectiveness of gargling binahong leaf solution on plaque index. This type of research is True Experiment research with a "one group pre-post test" design, conducted in June located at SD Negeri 21 Manado, Manado City. The total population of class III and IV students was 50 respondents with a total research sample population based on the inclusion criteria of 34 respondents. The instruments that will be used in this research are dental examination tools in the form of diagnostic sets, disclosing agents, personal protective equipment, plaque examination formats, mouthwash cups and precision digital scales. The data obtained was tabulated and analyzed using paired sample t-test. Based on the results of the Paired sample t test showing that there is a significant difference seen from the value of P = 0.000 (P<0.005), it can be concluded that H1: rinsing the mouth with binahong leaf solution is effective on the accepted plaque index.